Learners’ Perspective on Reading Comprehension Instructions in Small Group Discussion - Fanny Aprilia Sari; Mahda Lena; Prianti Wakhadiningrum; Ranti Ervianti (English Instruction, 2020)
The purpose of this study is to know students’ perspective about reading comprehension activities in small group discussions. The researcher conducted research related to reading comprehension in small group discussion activities. The researcher distributes a questionnaire form related to the subject to 15 students of class XI MIPA 6 SMAN 1 Pekanbaru. From this research, the result show get positive responses from 15 students of class XI MIPA 6 SMAN 1 Pekanbaru. The students gave the same answer that they ever been doing reading comprehension activities in small group discussion activities. The reading comprehension activities they carry out to help them in discussion activities to exchange opinions after understanding and interpreting reading information and then processing it to be easier to understand.